Finite element modeling of the electromechanical coupling in ionic polymer transducers - Akle, Barbar (2010)
Several researchers are actively studying Ionomeric polymer transducers (IPT) as a large strain low voltage Electro- Active Polymer (EAP) actuator. EAPs are devices that do not contain any moving parts leading to a potential large life time. Furthermore, they are light weight and flexible. An IPT is made of an ion saturated polymer usually Nafion, sandwiched between two electrodes made of a mixture of Nafion and electrically conductive particles usually RuO2 or platinum. Nafion is an acid membrane in which the cations are mobile while the anions are covalently fixed to the polymer structure. Upon the application of an electric potential on the order of 2V at the electrodes the mobile positive ions migrate towards the cathode leading to bending strains in the order of 5%. Our earlier studies demonstrate that the cations develop thin boundary layers around the electrode. Later developments in this finite element model captured the importance of adding particles in the electrode. This study presents the electromechanical coupling in ionic polymer transducers. Since all our earlier models were restricted to the electro-chemical part, here we will introduce the chemomechanical coupling. This coupling is performed based on previous studies (Akle and Leo) in which the authors experimentally showed that the mechanical strain in IPTs is proportional to a linear term and a quadratic term of the charge accumulated at the electrode. The values of the linear and quadratic terms are extracted from experimental data.